PENGGUNAAN SURAT IZIN PENANGKAPAN IKAN (SIPI) PALSU OLEH KAPAL ASING PENANGKAP IKAN - Alika Shanya Deivira Nofendi; Sri Untari Indah Artati (Fakultas Hukum Universitas Trisakti, 2023)
Every fishing activity requires a fishing permit (SIPI), yet as determined by Decision Number: 08/Pid.Prkn/2011/PN.TPI, foreign vessels continue to engage in fishing using forged licenses. The formulation of the issue in this study is compatibility between the legal repercussions for foreign ships that violate the SIPI falsification laws in the decision number 08/PID/PRKN/2011/PN.TPI and Law no. 45/2009 concerning amendments to Law no. 31/2004 concerning Fisheries, as well as what challenges foreign-flagged vessels encounter when making SIPI in order to use fake SIPI. Normative legislation is the study methodology used, using secondary data backed up by primary data. analysis of qualitative data leading to deduction. The study's findings and commentary demonstrate that from the conclusions of Article 94A jo. 28A Point B Law no. 45/2009 regarding changes to Law no. 31/2004 the fines imposed by the judges were not optimal and the constraints experienced by foreign-flagged vessels for fishing activities, since 2007 the Government of Indonesia has issued a policy regarding not extending fishing permits for foreign-flagged vessels.